Inflammation and Regeneration - Fujio, Keishi; Kumanogoh, Atsushi; Okano, Hideyuki; Mimori, Tsuneyo; Seino, Ken-ichiro.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Inflammation and Regeneration is the official journal of the Japanese Society of Inflammation and Regeneration (JSIR). This journal provides an open access forum which covers a wide range of scientific topics in the basic and clinical researches on inflammation and regenerative medicine. It also covers investigations of infectious diseases, including COVID-19 and other emerging infectious diseases, which involve the inflammatory responses. Inflammation research and regenerative medicine are tightly linked research areas in life sciences and their significance in translational research is rapidly increasing. From this aspect, this journal encourages the submission of manuscripts whose scope bridges these fields of research. The journal publishes papers in the following categories: research article, note, rapid communication, case report, review and clinical drug evaluation.
Keywords: Immunology; Cytology; Developmental biology; Inflammation; Nervous system$1 (BRegeneration.s; Immunology; Cell Biology; Developmental Biology and Stem Cells; Inflammation; Regeneration and Repair in the Nervous System